Immunotherapy, radiation oncology and radiology: An alliance into the future. Issue 4 (3rd June 2022) - Hau, Eric; Clements, Warren; Sia, Joseph
Abstract : AUTHOR BIOGRAPHIES: A/Prof Eric Hau is a clinician‐scientist with interest in lung and CNS tumours. His clinical and laboratory research focuses on understanding the mechanisms of radiation resistance and investigating drugs which may be utilised for radiation sensitisation to improve outcomes for patients. Associate Professor Warren Clements is an Interventional Radiologist at Alfred Health and has an Adjunct appointment with the Department of Surgery, Central Clinical School, Monash University. A/Prof Clements completed post‐fellowship subspecialty training in Interventional Radiology, consolidated by completion of the EBIR certification. A/Prof Clements is actively involved in medical research with over 80 peer‐reviewed publications, and has presented his research at national and international conferences. He is an Associate Editor for JMIRO and editorial board member of both CVIR and CVIR Endovascular. He volunteers his time for RANZCR as a member of the Interventional Radiology Committee and as an editorial board member for RANZCR's Inside Radiology website. A/Prof Clements has a keen interest in education and training, and is the supervisor of Intern Training in the Radiology Department. Dr. Joseph (Joe) Sia is a Consultant Radiation Oncologist at the Peter MacCallum Cancer Centre, Melbourne, Australia. He obtained his medical degree from the University of Otago, New Zealand and completed his radiation oncology training in Melbourne in 2017. He then undertook a laboratory‐based PhD in tumour immunology at the University of Melbourne, which was awarded in 2020.